Attitudes towards politics in Arequipa city: considering the regional and municipal elections for the year 2014 - Arias Gallegos, Walter (2018)
In the following research, we present a descriptive analysis of the application of an Attitudes towards Politics Questionnaire to a sample of 875 people who live in Arequipa City. The sample consists of 416 men and 459 women, whose average age is 38 years old. The questionnaire has 11 items and two dimensions: (Governability and Political participation) with proper levels of validity and reliability (α= 0.730). The results indicate that attitudes towards politics are negative, from which attitudes towards Politics participation are more positive than towards Governability.